The Development a 3D English Module for English Lesson in 4Th Grade in Elementary School - Hidayati, Anis Rohmah; Ningrum, Ary Setya Budhi; Suci, Dewi Nur (English Education:Journal of English Teaching and Research, 2022)
English teaching at an elementary school in Indonesia has experienced some changes in the curriculum in 2013. Based on the curriculum, 2013 is not obliged to teach English to students, so English lessons become a local subject that teaches material based on KI (Kompetensi Inti) and KD (Kompetensi Dasar). The teacher applies local content learning based on KI and KD because it is in accordance with the achievement target and is directed and structured according to the age level. That statement makes the current research to develop a module to help students easily study. The module that the current research develops is a character-based, three-dimensional module. In accordance with its research goals, this study used the ADDIE research and development (R&D) methodology (Analysis, Design, Development, Implementation, and Evaluation). The findings of this study demonstrates the need to gather expert and student input to determine whether product development is both practical and valid. 1) Validation by material and linguistic experts receives 87.3%, meeting the criteria for a good product that is genuine and does not require change; 2) Media expert validation received 96.6% of the vote; thesuperior product criterion is very valid and does not require adjustment; 3) The student evaluation of the product trial received 87.62%, with the criterion being a good product. The meaning is valid and does not require revision. Based on the findings, this study can be concluded that research hopefully can help students understand English lessons, so the students can improve their motivation to study English.